Antimicrobial Activity of Lactobacillus Species Against Carbapenem-Resistant Enterobacteriaceae - Chen, Chi-Chung; Lai, Chih-Cheng; Huang, Hui-Ling; Huang, Wen-Yu; Toh, Han-Siong; Weng, Tzu-Chieh; Chuang, Yin-Ching; Lu, Ying-Chen; Tang, Hung-Jen (Frontiers in Microbiology, 2019)
Objectives: This study aims to identify suitable lactobacilli that have anti-carbapenem-resistant Enterobacteriaceae (CRE) activity with in vitro tolerance to pepsin and bile salts. Methods: Fifty-seven Lactobacillus spp. strains encompassing nine species were collected for investigation. Their viabilities in the presence of pepsin and bile salts were tested using tolerance tests. Their anti-CRE effects were assessed by agar well diffusion and broth microdilution assay, as well as time-kill test. Results: Of the 57 Lactobacillus isolates collected, 31 had a less than 2-log reduction in their viability in both pepsin and bile salt tolerance tests. Of these 31 isolates, 5 (LUC0180, LUC0219, LYC0289, LYC0413, and LYC1031) displayed the greatest anti-CRE activity with a CRE zone of inhibition greater than 15 mm in agar well diffusion assays. The minimal inhibitory percentages of supernatants from these five strains against CREs ranged from 10 to 30%. With the exception of LUC0180, which had a minimal bactericidal percentage  40%, the bactericidal percentage of all the strains ranged from 20 – 40%. The inhibitory effect of the cell-free culture supernatants from these Lactobacillus strains did not change after heating but was abolished as the pH changed to 7.0. After a 24-h incubation, five of the Lactobacillus strains at a concentration of 108 CFU/ml totally inhibited the growth of carbapenem-resistant E. coli (CRE316) and K. pneumoniae (CRE632). After a 48-h incubation, the growth of CRE316 was completely inhibited under each concentration of lactobacilli based on time-kill test. Furthermore, when the concentration of lactobacilli was at 108 CFU/ml, the decline in pH was faster than at other concentrations. Conclusions: Some Lactobacillus strains exhibit anti-CRE activity, which suggests potential applications for controlling or preventing CRE colonization or infection.